The effect of extraction method on antioxidant content and activity of sesame oil - Mirghani, Mohamed E. S.; Hashim, Yumi Zuhanis Has-Yun; Ismail, Noornadia (2010)
The effects of extraction method of white and black sesame seeds on the activity of antioxidants in the oil have been investigated. Screening of extraction method (shake flask extraction and soxhlet extraction) on black and white sesame seeds shows that white sesame gave the highest antioxidant activity for both methods. The parameters that have been studied are the ratio of sea sand to sesame during size reduction (1:1, 1:3, 1:5), amount of sample (20 g, 30 g, 40 g) and time of extraction (4 hours, 6 hours, 8 hours) for both extraction methods; shake flask extraction and soxhlet extraction by using Box-Behnken under response surface methodology (RSM). Data has been analyzed using design expert and statistical analysis system software. The highest oil yield under optimized condition resulted in 59.94 % (w/w) for soxhlet extraction due to its countercurrent and repeated continues process. Determination of antioxidant activities under optimized condition were performed by total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging ability assay and ferric reducing antioxidant power (FRAP) assay. The highest oil yield, TPC and FRAP was obtained by soxhlet extraction at low ratio, high sample mass and time, which are 1:1, 40 g and 6 hour respectively. Further study need to be carried out in the future using different solvents.